The Design of Authenticated Telnet Protocol to Enhance Cryptography and Security - Yeh, Yi-Shiung; Lai, Wei-Shen (Malaysian Journal of Computer Science, 2002)
In this paper, an authenticated TELNET protocol is proposed to establish TELNET connections with authentication and security. To achieve this goal, specific cryptographic algorithms and certificates are used to resist attacks such as eavesdropping, tampering, forgery and personating. The concept of designing this proposed protocol is to negotiate one cipher spec (one suite of cryptographic algorithm) and to generate the shared secret. Then, apply them to protect the communication securely. As for extensibility, this system also provides a framework by means of which new cryptographic algorithms can be incorporated if necessary. In consideration of compatibility issue, we define the command names and codes following the rules of the TELNET protocol. Overall, this system enhances the security of TELNET protocol with NMAC, and it is compatible with the current TELNET protocol.